2001
DOI: 10.1590/s0021-75572001000200016
|View full text |Cite
|
Sign up to set email alerts
|

Uso de surfactante exógeno no tratamento da bronquiolite viral grave: relato de caso

Abstract: ResumoObjetivo: descrever os possíveis efeitos clínicos e laboratoriais da instilação traqueal de surfactante exógeno a um lactente com bronquiolite viral aguda grave e submetido a ventilação mecânica.Relato: menina de 2 meses de idade com diagnóstico clínico de bronquiolite viral aguda e submetida a ventilação mecânica, necessitando de altos picos de pressão inspiratória positiva (35 a 45 cmH 2 O) e elevada fração de oxigênio inspirado (FiO 2 = 0,9), sem resposta clínica favorável ou melhora na gasometria art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Vitola et al 53 have described the use of surfactant in a patient with severe acute viral bronchiolitis who needed high ventilation parameters to keep a PaO 2 of 60-80 mmHg. The use of surfactant (Exosurf Glaxo -50 mmHg) was followed by an improvement in ventilation and a reduction in the parameters used for that patient.…”
Section: Severe Viral Bronchiolitismentioning
confidence: 99%
“…Vitola et al 53 have described the use of surfactant in a patient with severe acute viral bronchiolitis who needed high ventilation parameters to keep a PaO 2 of 60-80 mmHg. The use of surfactant (Exosurf Glaxo -50 mmHg) was followed by an improvement in ventilation and a reduction in the parameters used for that patient.…”
Section: Severe Viral Bronchiolitismentioning
confidence: 99%
“…Vitola et al 53 , em nosso meio, descrevem a utilização de surfactante em um paciente com bronquiolite viral aguda grave que necessitava de elevados parâmetros ventilatórios para manter PaO 2 de 60-80 mmHg. A utilização de surfactante (Exosurf Glaxo -50 mmHg) seguiu-se de melhora da oxigenação e possibilidade de diminuição dos parâmetros utilizados no paciente.…”
Section: Bronquiolite Viral Graveunclassified
“…Several studies have shown lavage with diluted surfactant to be more therapeutically eff ective than conventional bolus or aerosol therapy (11)(12)(13). However, studies on pediatric and adult patients with diff erent indications for exogenous surfactant application have given contradictory results (14)(15)(16)(17)(18)(19)(20)(21)(22). For example, the use of surfactant shows promise for treating severe bronchiolitis and acute respiratory distress syndrome (ARDS) (23), but its use in patients with bronchopneumonia remains controversial.…”
Section: Introductionmentioning
confidence: 99%